Dominance Hierarchy Influences Adult Neurogenesis in the Dentate Gyrus - Kozorovitskiy, Yevgenia (J Neurosci, 2004)
Many mammalian species form dominance hierarchies, but it remains unknown whether differences in social status correspond to structural differences in the brain. Stressful experiences may arise naturally during the establishment of dominance, and stress has been linked to adult neurogenesis in the hippocampus. To determine whether position in a dominance hierarchy leads to changes in adult neurogenesis in the hippocampus, we examined the brains of rats housed in a visible burrow system (VBS), a seminaturalistic environment with opportunities for social interaction. Dominance hierarchies emerged among the males in all colonies within 3 d of living in the VBS. Although cell proliferation in the dentate gyrus did not differ between the groups, more new neurons were observed in the dentate gyrus of the dominant males compared with both subordinates and controls. Dominant and subordinate animals showed similar basal, stress, and recovery from stress levels of corticosterone, as well as similar thymus, adrenal gland, and body weights, suggesting that variables other than stress are responsible for the observed changes in adult neurogenesis. The differences in brain structure persisted among the animals that had no access to the burrow system after the dominance hierarchy stabilized, suggesting that social status rather than living in a complex environment accounts for the effect of dominance on adult neurogenesis.